Genetic Diversity Assessment in Pea (Pisum sativum L.) using Microsatellite Markers - Ram, Hanuman; Hedau, Nirmal K.; Chaudhari, Ganesh V.; Choudhary, Mukesh; Kant, Lakshmi (International Journal of Bio-resource and Stress Management, 2021)
The present study was conducted on genetic diversity analyses among 24 pea genotypes during 2017–2018 to assess the molecular diversity of pea genotypes using SSR markers. Out of 62, eleven markers were found to be polymorphic and the polymorphic information content (PIC) of the simple sequence repeat (SSR) markers ranged from 0.19 to as high as 0.64. Molecular profiling of these genotypes using 11 SSRs distributed throughout the genome generated 32 alleles with a mean of 2.91 alleles per locus. The genetic dissimilarity based on simple matching coefficient for 24 genotypes ranged from 0.00 to 0.91 with an average of 0.52. Cluster analyses grouped 24 genotypes into two major clusters with one outlier and supported by principal coordinate analysis (PCoA) in which genotypes were distributed across four quadrangles. Analysis of molecular variance (AMOVA) showed significant estimated value at degree of 1000 permutations. Percentage of variability was higher among individual (67%) than among populations (11%). Percentage of variability within individual was also higher (22%) than among populations (11%). Pop1 (I=0.707, He=0.446, and uHe=0.466) shows higher diversity than pop2 (I=0.630, He=0.381 and uHe=0.398). The percentage of polymorphic loci per population (PPL) ranged from 81.82% (pop2) to 90.91% (pop1) with an average of 86.36%. The present study demonstrates the utility of microsatellite markers for estimating molecular diversity as well as genotype identification in pea. This study also suggests a potential use of these markers in further association studies.